The development, implementation, and efficacy of a perioperative briefing communication and treatment planning tool and its adaptation to the COVID-19 pandemic. Issue 2 (10th December 2021) - Rassekh, Christopher H.; Atkins, Joshua H.; O'Malley, Bert W.; Chalian, Ara A.; Brody, Robert M.; Basu, Devraj; Paul, Ellen A.; Weinstein, Gregory S.
Abstract : Background: Effective communication and team alignment are critical elements in overall preparedness for surgery. We sought to assess staff perceptions of a newly implemented perioperative communication mechanism and evaluate its ongoing efficacy. Methods: A perioperative email briefing tool was developed as a virtual "huddle" process. A survey of the care team was then done after the first 6 months of its use. Implementation of the briefing for new faculty and a pandemic was observed. Results: After 6 months, all 4 head and neck surgeons had adopted this tool and utilized it for nearly 100% of cases, and the instrument was adopted by all other faculty subsequently joining the practice group. In the initial assessment, 98% of all respondents felt the process should continue. In a follow-up survey, over 88% believed the briefings reduced the risk of serious errors, near misses, and complications. Conclusions: An email perioperative briefing is feasible and improved workflow and safety.